2020
DOI: 10.1093/biolre/ioaa158
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine ameliorated TNF-α-induced primary trophoblast malfunction via muscarinic receptors†

Abstract: Oxidative stress and apoptosis of trophoblasts are involved in preeclampsia (PE). Numerous studies have shown that acetylcholine (ACh), the principal vagal neurotransmitter, plays a crucial role in attenuating oxidative stress, inflammation, and apoptosis in a variety of human diseases. However, the role of ACh in PE management remains unclear. Here, we aimed to determine the effects of ACh on TNF-α-treated human primary trophoblast cells. Western blotting, CCK-8, DHE, TUNEL immunofluorescence staining, transw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The acetylcholine is one of the metabolites synthesized by choline [ 34 ]. Several studies have stated that acetylcholine, acting as a neurotransmitter or an immune modulator, has beneficial effects on the reduction of the oxidative stress, inflammation and apoptosis in a variety of human diseases [ 35 , 36 ]. A recent study also suggested that acetylcholine is required for the acute inflammatory response [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acetylcholine is one of the metabolites synthesized by choline [ 34 ]. Several studies have stated that acetylcholine, acting as a neurotransmitter or an immune modulator, has beneficial effects on the reduction of the oxidative stress, inflammation and apoptosis in a variety of human diseases [ 35 , 36 ]. A recent study also suggested that acetylcholine is required for the acute inflammatory response [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…human diseases [35,36]. A recent study also suggested that acetylcholine is required for the acute inflammatory response [37].…”
Section: Plos Onementioning
confidence: 99%
“…Trophoblast dysfunction is central to the pathogenesis of PE through the action of TNF-α on trophoblast cells, and LPSinjected rats sustain injuries to trophoblast cells; the activation of NF-κB is then the inevitable result of the action of TNF-α and LPS (27)(28)(29)(30)32). It has been demonstrated in several studies that the NF-κB pathway was robustly activated in patients with PE (12,13), and the NF-κB pathway has thus been identified as a potential signaling pathway in the treatment of PE by improving trophoblast function or symptoms in animal models (55).…”
Section: Discussionmentioning
confidence: 99%
“…The immortalized human first-trimester trophoblast cell-line HTR-8/SVneo cells (ATCC, Rockville, MD, USA) were grown in RPMI 1640 medium (Gibco, Rockville, MD, USA) containing 10% fetal bovine serum (FBS; Gibco, Rockville, MD, USA) in a humid environment containing 5% CO 2 and 95% air at 37 • C. Different concentrations of AEDPPE (1, 5, 10, and 20 µM) were used to stimulate HTR-8/SVneo cells for 24 h. For the treatment of HTR-8/SVneo cells, TNF-α obtained from Sigma-Aldrich (T6674-10UG; St. Louis, MO, USA) was dissolved in double-distilled water, and TNF-α at 20 ng/ml was used to induce inflammation and dysfunction of HTR-8/SVneo cells (27)(28)(29)(30).…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation